First experience of salvage HDR brachytherapy after prostate cancer radiotherapy - Kišonas, Juras; Burneckis, Arvydas; Ivanauskas, Andrius; Mickevičius, Romualdas; Vėželis, Alvydas (Acta medica Lituanica, 2015)
Introduction. Prostate cancer (PC) is the most common oncologic disease among men. The number of patients with recurrent PC after primary radiotherapy is increasing, unfortunately, criteria for the choice among different treatment methods for these patients have not been defined yet. Salvage treatment options include prostatectomy, brachytherapy (BT), cryotherapy, thermoablation, and high frequency ultrasound. The lack of long-term evaluation of the toxicity and influence on the survival of patients after salvage high-dose-rate (HDR) BT is an important problem when considering this treatment option. In this study we have analyzed the treatment results of twelve patients who were diagnosed with local recurrent prostate cancer after primary radiotherapy and then treated with HDR BT. Materials and methods. Patients were treated with salvage HDR BT between January 2013 and February 2014 at the Institute of Oncology, Vilnius University Results. Average age of the patients at the time of salvage treatment was 67.5 years (min 54 years, max 76 years). The PSA value at the salvage treatment was from 2.06 ng/ml to 9.20 ng/ml. The time from the initial diagnosis till the salvage treatment was from 33 months to 134 months. All 24 procedures were successful and without any early complications. Conclusions. HDR BT is a presumable and safe treatment option for local prostate cancer recurrence after primary radiotherapy. Prospective clinical trial is initiated to evaluate survival, long-term toxicity and predictive value of different biomarkers.
Keywords: prostate cancer; salvage HDR brachytherapy; primary radiotherapy